How Natural are Conceptual Anaphors? - Oakhill, Jane (Lang Cogn Process, 1992)
This paper reports three experiments on the interpretation of “conceptual” anaphors. These are anaphors that do not have an explicit linguistic antecedent, but one constructed from context. For instance, if one says “I need a knife. Where do you keep them?”, them means something like “the knives that I presume you have in your house”. In the first experiment, subjects rated sentences containing conceptual anaphors, of three different types, to be as natural as ones with a “linguistically correct” antecedent (e.g. “I need an iron. Where do you keep it?”), and as more natural than ones with neither a plausible conceptual antecedent nor a plausible linguistic one. In a second (self-paced) experiment, subjects judged whether the second sentence in such pairs was a sensible continuation from the first, and the time to make these judgements was measured. We found that acceptability judgements were high, and judgement times low, in just those sentences that were rated as more natural in the first experiment. These first two experiments showed that conceptual anaphors are quite easily understood. However, they did not show that such anaphors are processed without difficulty. In the third experiment, we therefore compared conceptual anaphors (“plate … them”) with matched plural anaphors whose antecedents were explicit (“some plates … them”). The results were different for different types of anaphor: in one case (pronouns that referred to collective sets), the conceptual version followed by a plural pronoun was easier than the explicit plural version. For the other two types (references to generics and to implied multiple items), the explicit plurals were understood more rapidly than their conceptual counterparts.